Psychosocial Risk Screening of Children Newly Diagnosed With Type 1 Diabetes: A Training Toolkit for Healthcare Professionals - David Schwartz; Marni Axelrad; Barbara Anderson (Association of American Medical Colleges, 2013)
Abstract This training toolkit is an outgrowth of a training program we developed to teach clinicians to conduct psychosocial risk screenings of children and adolescents newly diagnosed with Type 1 diabetes, one of the most common (and challenging) chronic illnesses in childhood. When we began the screening program in 2007, we focused on training psychology graduate students enrolled in our predoctoral internship. Since then, interest in psychosocial screening has grown among other medical clinics in our hospital, and it became apparent that the need could not be met by Psychology interns alone. Indeed, as recently noted by Cameron and Northam (2012), psychology resources are a scarce commodity in many medical settings. We therefore designed this toolkit to provide healthcare professionals and learners from many different backgrounds (e.g., Medicine, Nursing, and Social Work, as well as Psychology) with the training and tools necessary to conduct psychosocial screenings competently and effectively in a pediatric setting. The toolkit is a comprehensive resource that can be used as a self-teaching resource for experienced professionals, or for training faculty to use to teach graduate and medical students. Included in the toolkit are 1) a Clinician Training Manual, with all of the necessary materials and tools to complete screenings as well as a self-assessment tool, and 2) a Supervisor's Guide that includes a detailed training curriculum and a standardized Checkout Rating procedure for evaluating learners' readiness to conduct screenings independently. Also included are the semi-structured interview forms used to conduct screenings, and guides to triage and intervention. Our hope is that dissemination of these materials will help psychosocial screening become more widely adopted as the standard of care for all children and youth diagnosed with Type 1 diabetes. Over the past six years, we have trained over twenty predoctoral interns and three postdoctoral fellows in clinical psychology. The training procedures were formalized into this toolkit over the past year, which was then piloted with four Psychology interns, one nurse practitioner, and two social workers. In addition, three Psychology postdoctoral fellows have been trained as instructors/ supervisors using these materials. Feedback was solicited from seven of these participants. All of the participants (100%) felt that all four learning objectives were met. Feedback was also collected on open-ended questions. In terms of the most valuable things learned from the training program, participants reported learning or gaining: "about the potential risk factors that might interfere with treatment adherence." "about the medical and psychosocial issues related to diabetes and the factors that influence adherence." "to incorporate MI [motivational interviewing] strategies to gain more accurate information on diabetes management." "about the psychosocial factors that impact a family with a child with diabetes [which] was important since this is such a prevalent medical condition." "a range of family responses to new diagnosis ... and how to triage." Participants also reported having gained the following from the program: "exposure to working in the inpatient setting, practice in modifying my clinical approach to match the family's response to the diagnosis and coping style and became more competent at educating the families about diabetes from a psychosocial perspective." "a greater understanding of 'miscarried helping' and the interaction cycle between parents and children with diabetes." The supervisors who used the submitted materials provided the following feedback: "The overall experience of training interns in conducting brief, evidence-based screens was very helpful. Supervising someone in conducting a brief screen helped me to refine my own clinical skills and to highlight the important aspects of the screening process. Further, I feel that having the supervision experience with these screens is generalizeable and I would be able to participate in other screening development processes." "Supervision and teaching are a large part of my training goals and this experience fulfilled those needs." Respondents provided the following feedback on the program materials: "I think they were helpful." "I found the materials to be very helpful." "The forms were helpful because they provided specific markers of skills to observe and rate. The teaching tools are great!" "The rating form is lengthy and perhaps with time if some portions of the form are deemed not as necessary as others, the length could be reduced."